Alkanethiol-Mediated Cyclization of o-Alkynylisocyanobenzenes: Synthesis of Bis-Thiolated Indole Derivatives - Kannika La-Ongthong (2020)
Copyright © 2020 American Chemical Society. Reactions of o-alkynylisocyanobenzenes with a variety of alkanethiols (Alk-SH) provide the corresponding bis-thiolated indole derivatives. The advantages of the reaction include metal-free, room-temperature, mild reaction conditions and broad functional group compatibility. The reaction proceeds via nucleophilic addition of an alkanethiol to an isonitrile moiety, 5-exo cyclization, followed by nucleophilic addition of an alkanethiol to a 3-alkylidene indole intermediate. Density functional calculations on the electronic structures and relative free energies of 5-exo and 6-endo cyclization pathways support that the 5-exo cyclization is preferable.